2022
DOI: 10.1136/bmjopen-2021-057774
|View full text |Cite
|
Sign up to set email alerts
|

How did communities in North West England respond to the COVID-19 lockdown? Findings from a diary study

Abstract: ObjectivesDuring the COVID-19 pandemic, the UK government and public health leaders advocated for community level responses to support vulnerable people. This activity could be planned and co-ordinated, however much was informal and developed organically. The effects on the individuals who were involved in providing and receiving informal support and implications for their communities have not been widely explored. The aim of this study was therefore to document and explore the nature, potential effects and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Other studies in the general population, also found that support emerged from communities across England during the COVID-19 pandemic to provide practical and essential help to residents (e.g. help with shopping, prescription deliveries) ( Ellis, Wilson, McCabe, & Macmillan, 2022 ; Ward et al, 2022 ). Stronger community responses tended to be among more cohesive communities and those with stronger relationships with their local authoriries ( Ellis et al, 2022 ).…”
Section: Discussionmentioning
confidence: 98%
“…Other studies in the general population, also found that support emerged from communities across England during the COVID-19 pandemic to provide practical and essential help to residents (e.g. help with shopping, prescription deliveries) ( Ellis, Wilson, McCabe, & Macmillan, 2022 ; Ward et al, 2022 ). Stronger community responses tended to be among more cohesive communities and those with stronger relationships with their local authoriries ( Ellis et al, 2022 ).…”
Section: Discussionmentioning
confidence: 98%